2021
DOI: 10.1155/2021/5575524
|View full text |Cite
|
Sign up to set email alerts
|

The Location of the Fibular Tunnel for Anatomically Accurate Reconstruction of the Lateral Ankle Ligament: A Cadaveric Study

Abstract: We aimed to describe the location of fibular footprint of each anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL), as well as their common origin in relation to bony landmarks of the fibula in order to determine the location of the fibular tunnel. In 105 ankle specimens, the center of the footprints of the ATFL and CFL (cATFL and cCFL, respectively) and the intersection point of their origin (intATFL-CFL) were investigated, and the distances from selected bony landmarks (the articular tip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(56 reference statements)
0
9
1
Order By: Relevance
“…A cadaveric study confirmed the reliability of the lateral malleolus as a skin marker for the distal insertion of the central beam [21]. The precision of the fibular insertions of the anterior talofibular ligaments (ATFL) and calcaneofibularis (CFL), as well as their common origin with respect to the bony landmarks of the fibula, are necessary to determine the location of the fibular tunnel in reconstructive surgery [22]. The results obtained in the current study are relatively close and, on average, are 6.2 ± 0.9mm.…”
Section: Discussionmentioning
confidence: 86%
“…A cadaveric study confirmed the reliability of the lateral malleolus as a skin marker for the distal insertion of the central beam [21]. The precision of the fibular insertions of the anterior talofibular ligaments (ATFL) and calcaneofibularis (CFL), as well as their common origin with respect to the bony landmarks of the fibula, are necessary to determine the location of the fibular tunnel in reconstructive surgery [22]. The results obtained in the current study are relatively close and, on average, are 6.2 ± 0.9mm.…”
Section: Discussionmentioning
confidence: 86%
“…The precise origin and insertion areas of the ligaments may help the surgeon to locate the bony tunnel. Thus, it is important to know the origin and insertion point for correct anatomic reconstruction 17 . Several studies focused on the attachment areas of each lateral ankle ligament in various aspects not only for providing the basic anatomical knowledge but also in terms of clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the minimal invasive surgical procedure was used to treat the CLAI providing the good view to define the ligaments 7,8 . In both percutaneous and arthroscopic surgical approaches for treating the CLAI, a single fibular tunnel with a shared origin site for the ATFL and CFL is required 17 . However, understanding how ligaments are attached helps with more precise positioning of the tunnel for repair or reconstructions.…”
Section: Introductionmentioning
confidence: 99%
“…The anatomic measurements in this study indicated that the tunnel locations might be slightly lower than which described by Lan et al Bony landmarks, such as the inferior tip of the fibula and fibular obscure tubercle, have been widely used in anatomical studies to assess the fibular insertions of the ATFL and CFL. The distance from ligamentous attachments to the inferior tip of the fibula varied in the literature, 2,4,17,24,25,27,34 whereas the fibular obscure tubercle was available and reliable for identifying the attachments of the ATFL and CFL. 23 Using the distal fascicle of the AITFL, the locations of the ATFL and CFL corresponded with the fibular obscure tubercle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intersection point of the ATFL and CFL (intATFL-CFL) in the fibula was identified by minimal dissection of the most inferior and posterior fibers of the ATFL and the most anterior fiber of the CFL (Figure 2). 24 Two observers performed all measurements to calculate the intraclass correlation coefficients (ICCs). Each observer measured the distances using a caliper 3 times to calculate the mean values.…”
Section: Methodsmentioning
confidence: 99%